Relationship between vertical jumping ability and endurance capacity with internal training loads in professional volleyball players during preseason - Berriel, Guilherme P. (2022)
BACKGROUND: This study aimed to quantify internal training load and changes in vertical jumping ability and endurance capacity of professional volleyball players during the preseason, and to explore relationships between players' physical qualities at the beginning of the preseason with internal training load accumulated during the first two weeks of training. METHODS: Sixteen male professional volleyball players from a team participating in the Brazilian National Super League took part in the study. Before and after a 10-week preseason, their vertical jumping ability and endurance capacity were assessed by squat jump, countermovement jump without and with arm swing, and YoYo endurance test, level 1. The internal training load was quantified by the session rating of perceived exertion method. Results were analyzed using analysis of variance, magnitude-based inference and Pearson's correlation. RESULTS: The internal training load varied between 1388±111 arbitrary units (a.u.) and 3852±149 a.u., and performance in all the tests was positively changed (small to moderate effect sizes) at end of preseason training. Significant (P<0.05) very large and large correlations were observed between squat jump (r=-0.81) and YoYo endurance test (r=-0.64) performances and internal training load accumulated during the first two training weeks, respectively. CONCLUSIONS: The internal training load and training strategies undertaken by the investigated team were effective to improve players' vertical jumping ability and endurance capacity. Coaches need to improve these physical qualities of volleyball players in order to improve their tolerance to training.